Outcome of a salvage third autologous stem cell transplantation in multiple myeloma - Garderet, Laurent; Goldschmidt, Hartmut; Schönland, Stefan (Biology of blood and marrow transplantation, 2018)
To evaluate the outcomes of salvage third autologous stem cell transplantation (ASCT) in patients with relapsed multiple myeloma. We analyzed 570 patients who had undergone a third ASCT between 1997 and 2010 (European Society for Blood and Marrow Transplantation data), of whom 482 patients underwent tandem ASCT and a third ASCT at first relapse (AARA group) and 88 patients underwent an upfront ASCT with second and third transplantations after subsequent relapses (ARARA group). With a median follow-up after salvage third ASCT of 61 months in the AARA group and 48 months in the ARARA group, the day +100 nonrelapse mortality in the 2 groups was 4% and 7%, the incidence of second primary malignancy was 6% and 7%, the median progression-free survival was 13 and 8 months, and median overall survival (OS) was 33 and 15 months. In the AARA group, according to the relapse-free interval (RFI) from the second ASCT, the median OS after the third ASCT was 17 months if the RFI was <18 months, 37 months if the RFI was between 18 and 36 months, and 64 months if the RFI was ≥36 months (P < .001). In the ARARA group, the median OS after the third ASCT was 7 months if the RFI was <6 months, 13 months if the RFI was between 6 and 18 months, and 27 months if the RFI was ≥18 months (P < .001). In a multivariate analysis of the AARA group, the favorable prognostic factor was an RFI after second ASCT of ≥18 months. Progressive disease and a Karnofsky Performance Status score of <70 at third ASCT were unfavorable factors. A salvage third ASCT is of value for patients with relapsed myeloma, particularly for those with a long duration of response and chemosensitive disease at the time of transplantation.